2008
DOI: 10.1186/1744-9081-4-31
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in children with chronic protein energy malnutrition

Abstract: Background: Malnutrition is associated with both structural and functional pathology of the brain. A wide range of cognitive deficits has been reported in malnourished children. Effect of chronic protein energy malnutrition (PEM) causing stunting and wasting in children could also affect the ongoing development of higher cognitive processes during childhood (>5 years of age). The present study examined the effect of stunted growth on the rate of development of cognitive processes using neuropsychological measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
220
2
22

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(261 citation statements)
references
References 30 publications
17
220
2
22
Order By: Relevance
“…Recent studies show that children who failed to thrive in infancy are lighter and shorter at school age with adverse intellectual outcomes (Corbett and Drewett, 2004;Black et al, 2007;Emond et al, 2007;Kar et al, 2008). Weight faltering in the first few months of life is particularly associated with these adverse effects.…”
mentioning
confidence: 99%
“…Recent studies show that children who failed to thrive in infancy are lighter and shorter at school age with adverse intellectual outcomes (Corbett and Drewett, 2004;Black et al, 2007;Emond et al, 2007;Kar et al, 2008). Weight faltering in the first few months of life is particularly associated with these adverse effects.…”
mentioning
confidence: 99%
“…Early-onset FTT has been found to increase children's vulnerability to short stature, poor arithmetic performance and poor work habits (Black et al, 2007;Kar et al, 2008). Although the concept of FTT is widely used, no consensus exists regarding its specific definition.…”
Section: Monitoring Growthmentioning
confidence: 99%
“…Any imbalance can have both short-and long-term consequences. For example, Kar et al (2008) showed cognitive impairment in children with chronic protein energy malnutrition (Kar et al, 2008). In addition, protein depletion may affect prognosis with regard to liver transplants and tolerance to chemotherapy, and thus also the clinical outcomes.…”
Section: Main Cause Of Growth Falteringmentioning
confidence: 99%
“…Severe acute malnutrition (SAM) is a leading cause of global child mortality, is associated with growth faltering, and results in impaired cognitive development (Kar et al 2008). A significant proportion of deaths due to numerous illnesses including malaria, measles and diarrheal diseases have also been attributed to malnutrition (Caulfield et al 2004).…”
Section: Introductionmentioning
confidence: 99%